PEDAGOGIKA OGÓLNA JAKO SUBDYSCYPLINA NAUKOWA - Muszyński, Heliodor (Wydawnictwo Naukowe UAM w Poznaniu, 1997)
The article takes up the issue of the development and shape of general pedagogy as a sub-discipline within pedagogical sciences. The author provides a critical analysis of views describing reasons for its crisis in Poland. Falsity of those views was caused by applying the ipsative approach, requiring to consider a given phenomenon as a unique one. The application of the normative approach allows to use a broader perspective in a few aspects: global (the range of the whole discipline), study of science (covering changes in science as a whole), and evolution (considering phenomena in their historical continuity and change). The analysis described allows to distinguish some steps in the development of science, which can be fully applied to the case of general pedagogy in reference to one country (Poland).
Keywords: Pedagogika ogólna; Kryzys pedagogiki; Problemy globalne; Subdyscypliny naukowe; General pedagogy; Pedagogy crisis; Global problems; Scientific subdiscipline; Neodidagmata